Food, Our Common Ground: A Photovoice Study - Malova, Ekaterina; Aerpati, Abuduaihaiti; Mao, Bingjing; Shah, Kinza; Tian, Shiyun; Zhang, Zhiwei; Harrison, Tyler Ronald (Frontiers in Communication, 2021)
Research shows that factors like campus food environment, food accessibility, and acculturation may shape students’ eating patterns and influence their physical and emotional well-being. Although research has investigated factors that contribute to student food choices, few, if any, prior studies have examined this topic from the perspective of graduate students’ own experiences. By utilizing Photovoice methodology, the current study aims to fill the research gap as well as supplement the current literature, providing insights from graduate students’ everyday realities and feedback from policymakers. Three overlapping themes emerged across all images: 1) unhealthiness becomes the norm, 2) the convenience of food influences decisions, and 3) healthy food consumption a symbol of cultural identity. The feedback from university policymakers in relation to identified themes revealed two key issues. First, the information about dining options on campus is not visibly present anywhere on campus. Second, much of dining services is designed with undergraduate students in mind. The findings of this study suggested that universities should provide a better environment to promote healthy food consumption, improve students’ awareness of healthy options, make healthy options convenient enough to consume, limit students’ access to unhealthy food, and consider the needs of international students.